The gut microbial differences between pre-released and wild red deer: Firmicutes abundance may affect wild adaptation after release - Guo, Jinhao; Li, Zheng; Jin, Yongchao; Sun, Yue; Wang, Binying; Liu, Xinxin; Yuan, Ziao; Zhang, Weiqi; Zhang, Changzhi; Zhang, Minghai (Frontiers in Microbiology, 2024)
Insufﬁcient density of red deer has affected the stability of forest ecosystems and the recovery of large carnivores (represented by Amur tiger). Conservation translocations from captivity to the wild has become an important way to restore the red deer populations. However, the difference in gut microbes between pre-release and wild red deer may affect the feeding adaptability of red deer after release. In this study, we clarified the differences in gut microbes between pre-released and wild red deer and screened the key gut microbes of the red deer involved in feeding by using metagenomic sequencing and feeding analysis. The results showed that the microbial difference between pre-released and wild red deer was mainly related to Firmicutes represented by Eubacteriales and Clostridia, and Firmicutes abundance in pre-released red deer (68.23%) was significantly lower than that of wild red deer (74.91%, p < 0.05). The expression of microbial metabolic pathways in pre-released red deer were significantly lower than those in wild red deer (p < 0.05), including carbohydrate metabolism, amino acid metabolism, glycan biosynthesis and metabolism, etc. The combinations of Firmicutes were significantly positively correlated with the intake of plant fiber and carbohydrate (p < 0.05), and were key microbes to help red deer deal with wild plant resources. Additionally, the combinations of Firmicutes represented by Eubacteriales and Clostridia lacking in pre-released red deer contributed the most to expression of microbial metabolic pathways (importance＞1), showing a significant positive correlation (p < 0.05). This study indicates that high abundance of Firmicutes is an important guarantee for red deer to adapt to the wild feeding environment, which provides critical implications for the recovery of red deer populations and the protection of endangered ungulates.